Impacts of ainuovirine-based and efavirenz-based antiretroviral therapies on the lipid profile of HIV/AIDS patients in southern China: a real-world study - Zhang, Quan; Chen, Zhong; Wang, Yating; Peng, Yongquan; Tan, Si; Li, Ying; Cao, Guiying; Bignotti, Antonia; Wu, Shangjie; Wang, Min (Frontiers in Medicine, 2024)
Background The newly approved third-generation oral anti-HIV-1 drug, ainuovirine (ANV), was used in combination with nucleoside reverse transcriptase inhibitors (NRTIs) in our study, and its effects on the lipid profile of antiretroviral-experienced HIV/AIDS patients are unclear. Objectives This study aimed to examine the effects of antiretroviral agents on the lipid profile in patients with HIV/AIDS. Methods We conducted a real-world prospective study involving treatment-naive and treatment-experienced adult participants living with HIV-1 infection provided with ANV- or efavirenz (EFV)-based regimens. The primary endpoint was the proportion of participants with an HIV-1 RNA level of <50 copies/mL at week 24 of treatment. Secondary endpoints included the change from baseline in CD4+ T-cell count and lipid profile. Results A total of 60 treatment-naive and 47 treatment-experienced participants received an ANV-based regimen, while 88 treatment-naive and 47 treatment-experienced participants receiving an EFV-based regimen were, respectively, matched as controls. At week 24 following treatment, the proportion of participants with an HIV-1 RNA level of <50 copies/mL and the mean changes of CD4+ T-cell counts from baseline were significantly higher in naive-ANV group than those in naive-EFV group (p < 0.01). Compared with the EFV group, both naive and experienced ANV groups exhibited a favorable lipid profile, including constant changes in total cholesterol and triglycerides, a significant decrease in LDL-cholesterol (p < 0.0001), and a dramatic increase in HDL-cholesterol (p < 0.001). Conclusion The efficacy of ANV was non-inferior to EFV when combined with two NRTIs. Patients receiving ANV-based regimens had a decreased prevalence of dyslipidemia.